CONCEPT OF ECOLOGICAL ARCHITECTURE ON THE DESIGN AND CONSERVATION OF LAKE ISTN JAKARTA - Maulina Dian Purwanti; Ima Rachima Nazir (Dinasti Publisher, 2022)
Within the life of the academic community on campus, especially for students, there are various activities in addition to the main activities, lectures. These other activities require facilities that support continuity of activities that can also increase the development of students' interest, passion, and talent. One of the locations on the National Institute of Science and Technology (ISTN) campus that can be used for one of the activities is a lake located in the middle of the campus but has not been designed to be able to utilize the potential of the lake optimally. Moreover, the position of the ISTN lake located in the urban area of South Jakarta is expected to be maintained as a water catchment and physically classified as natural reservoir. As a consideration for the design, it is necessary to pay attention to the condition of the lake that is starting to be concerning because the shallower the depth of the lake and the smaller the area of the lake due to the absence of plastering while paying attention to the ecosystem. How would the design be able to utilize the potential of the lake for various activities, as well as lake conservation in order to maintain it as a natural water catchment and reservoir. For this reason, lake design is directed to the utilization of lake potential and lake conservation aimed at seeking the use of the lake for academic and community activities and the realization of the sustainability of biological natural resources and the balance of ecosystems. In the design above will be implemented the concept of Ecological Architecture that seeks to do environmental arrangement by utilizing the potential or natural resources and use of technology based on environmentally friendly ethical management